Dual-modal photoacoustic and magnetic resonance tracking of tendon stem cells with PLGA/iron oxide microparticles in vitro - Lu, Man (PLoS One, 2018)
Reliable cell tracking is essential to understand the fate of stem cells following implantation, and thus promote the clinical application of stem cell therapy. Dual or multiple modal imaging modalities mediated by different types of multifunctional contrast agent are generally needed for efficient cell tracking. Here, we created a new contrast agent—PLGA/iron oxide microparticles (PLGA/IO MPs) and characterized the morphology, structure and function of enhancing both photoacoustic (PA) and magnetic resonance imaging (MRI). Both PA and MRI signal increased with increased Fe concentration of PLGA/IO MPs. Fluorescent staining, Prussian blue staining and transmission electron microscope (TEM) certified that PLGA/IO MPs were successfully encapsulated in the labeled TSCs. The established PLGA/IO MPs demonstrated superior ability of dual-modal PA/MRI tracking of TSCs without cytotoxicity at relatively lower Fe concentrations (50, 100 and 200 μg/mL). The optimal Fe concentration of PLGA/IO MPs was determined to be 100 μg/mL, thus laying a foundation for the further study of dual-modal PA/MRI tracking of TSCs in vivo and promoting the repair of injured tendon.